Non-Hodgkin Lymphoma Relapse Presenting as Isolated Neurolymphomatosis of the Brachial Plexus - A Case Report - Parashar, Yatendra; Hasan, Faheema; Bishnu, Arijit; Kashyap, Rajesh (Indian Journal of Medical and Paediatric Oncology, 2020)
Neurolymphomatosis is a rare manifestation of non-Hodgkin's lymphoma (NHL) and is characterized by infiltration of the nerves by neoplastic lymphoid cells and is seen in up to 0.2% of all NHL cases. Diagnosing this syndrome is quite a challenge to the hematologists given the vague symptoms and signs and the low incidence. Newer imaging modalities such as positron emission tomography–computed tomography and magnetic resonance imaging have enabled early diagnosis with a sensitivity reaching up to 100%. Despite a variety of therapies reported in the literature for the treatment, the prognosis is very poor. We report a 46-year-old male diagnosed to have NHL–diffuse large B-cell lymphoma and treated with rituximab, cyclophosphamide, vincristine, and prednisolone (R-CHOP) therapy who presented with left brachial plexus neurolymphomatosis as the initial feature of disease relapse.
Keywords: Brachial plexus; chemotherapy; neurolymphomatosis; non-Hodgkin's lymphoma